Injuries among Swedish female elite football players: a prospective population study - Jacobson, I.; Tegner, Y. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Injury occurrence in all 12 female elite senior football teams in premiere league was registered during 1 year. Of 269 players, 129 (48%) sustained 237 injuries. The total injury incidence was 4.6/1000 h of football. The injury incidence during practice was 2.7 and during the game time was 13.9/1000 h. The highest injury incidence during practice was to the knee (0.8/1000 h) and thigh (0.5/1000 h), and during game time was to the knee (4.4/1000 h) and head (2.2/1000 h). In total, the location for the highest injury incidence was the knee with 1.5 injuries/1000 h of football.